Morphological Characters Analysis, the Intergroup Phylogenetic Relationships and Possible Outgroups of the Family Sphaeriidae (Mollusca, Bivalvia) - Korniushin, A.V. (Вестник зоологии, 2002)
Scenaria of the morphological characters transformations in freshwater molluscs traditionally included in the family Sphaeriidae are studied; they are based on the phylogenetic analysis of 69 characters in 57 taxa. Рассмотрены сценарии эволюционных преобразований морфологических признаков пресноводных моллюсков, традиционно включаемых в семейство Sphaeriidae, основанные на результатах филогенетического анализа 69 признаков в 57 таксонах.